Antibacterial Activity Of Fresh Juices Of Allium Cepa And Zingiber Officinale Against Multidrug Resistant Bacteria - G. O. ADESHINA; S. JIBO,; V.E. AGU; J. O. EHINMIDU (International Journal of Pharma and Bio Sciences, 2011)
Antibiotic resistant bacteria are one of the major problems challenging the health care system in general. The antibacterial activity of fresh red and white Allium cepa (Onion) and Zingiber officinale (Ginger) juices against multidrug resistant bacteria viz: Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli and Salmonella typhi isolated from salad was investigated using agar well diffusion and agar dilution methods. All the bacteria except Staphylococcus aureus were susceptible to the fresh red and white onion juices with the diameter of zones of inhibition ranging from 15mm – 35mm while the test bacteria isolates were not sensitive to the fresh ginger juice. The Minimum Inhibitory Concentration (M. I. C.) and the Minimum Bactericidal Concentration (M. B. C) values of the fresh onion juices against the test bacteria were low ranging from 3.125%v/v – 25.0% v/v. This study indicates that the fresh juices of Allium cepa possess significant antibacterial potency against multidrug resistant bacteria.